Penyuluhan Hukum Tentang Pengenalan Terhadap Teknis Penyusunan Produk Hukum Di Desa Ambaipua Kecamatan Ranomeeto Kabupaten Konawe Selatan - Muhammad Jufri; La Ode Muhammad Taufiq Afoeli; Hambali Husaini; Hidarni Hidarni; Baramansah Baramansah; Ahmad Syarid Miqdad (Indonesia Berdampak: Jurnal Pengabdian kepada Masyarakat, 2026)
This Community Service activity is entitled "Legal Counseling on an Introduction to the Technical Preparation of Legal Products in Ambaipua Village." The purpose of this community service activity is to increase the community's understanding and legal awareness regarding the Introduction to the Technical Preparation of Legal Products in Ambaipua Village, thereby providing an understanding of the mechanisms of village regulations and the hierarchy of legislation. The methods used during the community service activity include: (a) lectures to provide direct explanations of the counseling materials; technical training on the preparation of village legal products; and (b) a question-and-answer method to enable the community to gain as much knowledge as possible about the counseling materialsThe legal counseling successfully increased Village Officials' understanding of the hierarchy of legislation, provided technical skills in the preparation of village legal products, and enhanced their understanding of community participation and public consultation.